Knowledge management in theory & practice - Eliezer Geisler, Nilmini Wickramasinghe (2019)
This text provides a comprehensive introduction to the new field of knowledge management. It approaches the subject from a management rather than a highly technical point of view, and provides students with a state-of-the-art survey of KM and its implementation in diverse organizations. The text covers the nature of knowledge (tacit and explicit), the origins and units of organizational knowledge, and the evolution of knowledge management in contemporary society. It explores the implementation and utilization of knowledge management systems, and how to measure their impact, outputs, and benefits. The book includes a variety of original case studies that illustrate specific situations in which the absence or existence of knowledge management systems has been crucial to the organization's actions. Charts and figures throughout help clarify more complex phenomena and classifications, and each chapter includes review questions and a comprehensive index.